2014
DOI: 10.1038/mt.2013.238
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic HSV-mediated Oncolysis Shapes the Antitumor Immune Response and Contributes to Therapeutic Efficacy

Abstract: Within the oncolytic virus field, the extent of virus replication that is essential for immune stimulation to control tumor growth remains unresolved. Using infected cell protein 0 (ICP0)-defective oncolytic Herpes simplex virus type 1 (HSV-1) and HSV-2 viruses (dICP0 and dNLS) that show differences in their in vitro replication and cytotoxicity, we investigated the inherent features of oncolytic HSV viruses that are required for potent antitumor activity. In vitro, the HSV-2 vectors showed rapid cytotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 36 publications
4
104
0
Order By: Relevance
“…For some viruses (eg, T-vec, reovirus), this antitumor immune response can sometimes be more important than that of direct oncolysis where direct injection of the primary tumor is associated with regression of distant nodules. [28][29][30][31] Although cancer cells express tumor antigens, spontaneous rejection of tumors by cytotoxic CD8…”
Section: Discussionmentioning
confidence: 99%
“…For some viruses (eg, T-vec, reovirus), this antitumor immune response can sometimes be more important than that of direct oncolysis where direct injection of the primary tumor is associated with regression of distant nodules. [28][29][30][31] Although cancer cells express tumor antigens, spontaneous rejection of tumors by cytotoxic CD8…”
Section: Discussionmentioning
confidence: 99%
“…1 Conventional chemotherapy and radiotherapy achieve limited efficacies leading to the search for novel ways to treat cancer. 2 Oncolytic viruses selectively propagate in cancer cells while displaying minimal adverse effects in healthy cells, making it one of the most promising treatments. 3 For example, oncolytic herpes simplex virus type-1 (HSV-1) vector is a useful tool for treating solid malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…4 Studies in preclinical murine tumor models showed that the antitumor activity of the prototype HSV-1 ICP0-null OV KM100 depends on whether the tumor model is tolerized. 4,6 Although in vitro tumor cell cytotoxicity mirrors the in vivo therapeutic efficacy of some OVs, 7 we fail to observe a similar correlation with our herpesvirus-based OVs, 5,6,8 despite the requirement for replication of competent vectors. 4 Thus, the complex molecular interactions that dictate permissivity of oncolytic HSVs in cancer cells remain elusive.…”
Section: Introductionmentioning
confidence: 59%
“…3 We have developed and tested the efficacy of HSV-1 deleted for the viral protein ICP0 as oncolytic vectors. [4][5][6] These OVs show modest in vitro oncolysis mainly in cancer cell types with impaired abilities to mount anti-viral responses. 4 Studies in preclinical murine tumor models showed that the antitumor activity of the prototype HSV-1 ICP0-null OV KM100 depends on whether the tumor model is tolerized.…”
Section: Introductionmentioning
confidence: 99%